Post-2025 climate finance target: how much more and how much better? - Pauw, WP; Moslener, U; Zamarioli, LH; Amerasinghe, N; Atela, J; Affana, JPB; Buchner, B; Klein, RJT; Mbeva, KL; Puri, J; Roberts, JT; Shawoo, Z; et al. (Taylor and Francis, 2022)
Formal deliberations for the new collective quantified goal on climate finance began at COP26 in Glasgow. This Perspectives article aims to inform this process by discussing the potential size and nature of is post-2025 target. We argue that the climate finance system around the current target to mobilise US$100 billion per year to support developing countries has been fraught with difficulties, and that it would be ineffective to simply increase the climate finance target without addressing these difficulties. Therefore, we identify and discuss five priority elements for negotiations: the relation to Article 2.1(c) of the Paris Agreement; the adaptation-mitigation balance; financial instruments; mobilising private finance; and ‘new and additional’ finance. To increase transparency, accountability, and trust in climate finance under the UNFCCC and to simultaneously allow for the mobilisation of finance at scale, we suggest setting a sub-target for grants. In combination with additional (sub)target(s), this could define an overall new collective quantified goal that is better suited to serve the challenging dual role of mobilising finance at scale and transferring resources to developing countries.